2000
DOI: 10.1159/000008123
|View full text |Cite
|
Sign up to set email alerts
|

Pontine Atrophy in Spinocerebellar Ataxia Type 6

Abstract: To investigate the clinical range of spinocerebellar ataxia type 6 (SCA6), we screened CAG repeat expansion in the voltage-dependent alpha 1A calcium channel gene (CACNL1A4) in 71 ataxic patients in 60 families; 54 patients in 43 families with hereditary ataxia and 17 sporadic patients. Thirteen patients with SCA6 were detected to have elongated CAG in CACNL1A4. Of these, 7 patients had been diagnosed as having hereditary cerebellar cortical atrophy, and 6 patients had been found to have sporadic occurrence. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 31 publications
2
2
0
Order By: Relevance
“…In this study, we observed severe pontine atrophy in the patients with SCA7; this was much more prominent than in other types of SCA (SCA3 and SCA6) and was consistently found in patients with varying degrees of cerebellar atrophy and severity of illness. Pontine atrophy has been reported in other SCAs, even in SCA6, 18 although it is quite unexpected for such patients to have pontine atrophy with their cerebellum spared, which we found in our patients with SCA7. All patients with SCA7 may not have the neuroradiological characteristics observed in this study, yet pontine atrophy was a prominent finding in our patients with SCA7.…”
Section: Discussionsupporting
confidence: 62%
“…In this study, we observed severe pontine atrophy in the patients with SCA7; this was much more prominent than in other types of SCA (SCA3 and SCA6) and was consistently found in patients with varying degrees of cerebellar atrophy and severity of illness. Pontine atrophy has been reported in other SCAs, even in SCA6, 18 although it is quite unexpected for such patients to have pontine atrophy with their cerebellum spared, which we found in our patients with SCA7. All patients with SCA7 may not have the neuroradiological characteristics observed in this study, yet pontine atrophy was a prominent finding in our patients with SCA7.…”
Section: Discussionsupporting
confidence: 62%
“…Therefore, MRI results may enable physicians to conjecture the underlying mutations and to direct gene testing for these mutations. Pontine atrophy has been reported in other types of SCA, including SCA6 35,36 ; however, it is exceptional for such patients to have pontine atrophy with their cerebellum spared, which was observed in our patients with SCA7.…”
Section: Commentsupporting
confidence: 43%
“…Interestingly, the CACNA1A gene is also implicated in two other disorders, namely episodic ataxia type 2 (EA2) and chronic spinocerebellar ataxia type 6 (SCA6) (17,18). Both phenotypes also involve progressive cerebellar ataxia and atrophy (1921). In a small MRS study no differences were found in cerebellar tNAA/tCre ratios between EA2 patients and controls possibly because of lack of power (22), whereas MRS studies focusing on SCA6 showed a lower cerebellar tNAA/tCre ratio (23,24).…”
Section: Discussionmentioning
confidence: 99%